Improved two‐dimensional electrophoretic mapping of Japanese human hair proteins; application to curved and straight Japanese human hairs; and protein identification by MALDI MS and MS/MS quadrupole time‐of‐flight mass spectrometry. (5th July 2020) - Bryson, W.G.; McCormack, A.C.; Plowman, J.E.; Grosvenor, A.J.; Murphy, C.J.; Nagase, S.; Itou, T.; Koike, K.
Abstract: Objectives: To evaluate improved protein extraction and two‐dimensional electrophoresis (2DE) separation methods with Japanese reference human hair (JRH); to determine whether fibre curvature is related to protein composition in curly and straight Japanese women's human hair (JHH) samples; and to identify proteins from JRH 2DE maps and expression differences between curly and straight JHH. Methods: Hair keratin and keratin‐associated proteins (KAPs) were extracted intact with dithiothreitol or tris(2‐carboxyethyl) phosphine from JRH or from curved or straight JHH. Extracted proteins were isoelectric‐focused on first‐dimensional pH gradient gel strips, then separated by molecular weight on laboratory‐made, second‐dimension, large format gels. The software compared protein abundance between duplicate 2DE gels of curved and straight JHH. Thirty‐eight proteins from a JRH 2DE gel were enzyme‐cleaved for MALDI‐TOF‐MS analysis to determine peptide composition, and where possible, de novo sequencing gave peptide sequence data. An in‐house human hair protein database incorporating ninety‐eight annotated protein sequences assisted MS analysis. Results: 2DE gels of tris(2‐carboxyethyl) phosphine‐extracted JRH improved keratin and KAP resolution and number compared to those of dithiothreitol‐extracted JRH and published commercially made second‐dimensional gels. Silver‐stained 2DE gels of the straight or curved JHH sets were remarkably similar. Over‐staining to reveal basic proteins caused poor resolution of the major acidic protein classes. Software comparisons of fifty‐nine resolved proteins revealed two were significantly different in abundance between curved and straight hairs but in insufficient amounts for MS analysis. MS identified twelve proteins from a JRH CBBG‐stained 2DE gel: six type II keratins, three type I keratins and three high sulphur proteins. A further eight were potential conformational isoforms and isoelectric variants of the identified proteins bringing the total to twenty identified or partially identified proteins. Conclusion: Root‐end human hair extraction with tris(2‐carboxyethyl) phosphine improves protein resolution and visualizes more proteins on large format 2DE gels. The two minor protein differences between duplicate straight or curved JHH 2DE gels were unlikely to change fibre structure from straight to curved hair. MS results confirmed that multiple isoforms exist of various hair proteins. Low sequence coverage prevented distinction between members in rows of homologous protein spots of similar molecular weight. Abstract : Protein TCEP extracts of a curved Japanese human scalp hair sample set were separated on duplicate large format, silver‐stained 2DE gels (A and B) and compared to corresponding duplicate 2DE gels of a straight hair sample set (C and D). Protein abundance differences between the two gel sets were determined by densitometric quantitation and identified by MS along with other proteins of interest. Résumé: Objectifs: évaluer l'amélioration de l'extraction de protéines et les méthodes de séparation bidimensionnelle par électrophorèse (2DE) avec des cheveux humains de référence Japonais (JRH), déterminer si la courbure de la fibre est liée à la composition protéique dans les échantillons de cheveux humains des Japonaises (JHH) bouclés et raides et identifier les protéines issues des cartes JRH 2DE et les différences d'expression entre les JHH bouclés et raides. Méthodes: la kératine des cheveux et les protéines associées à la kératine (KAP) ont été extraites intactes avec du dithiothréitol ou du tris (2‐carboxyéthyl) phosphine des JRH ou des JHH bouclés ou raides. Les protéines extraites ont subi une focalisation isoélectrique sur des bandes de gel à gradient de pH unidimensionnelles, puis ont été séparées par poids moléculaire sur des gels bidimensionnels de grand format, fabriqués en laboratoire. Le logiciel a comparé l'abondance des protéines entre les deux duplicatas de gels 2DE des JHH bouclés et raides. Trente‐huit protéines provenant d'un gel 2DE JRH ont été clivés par enzyme pour l'analyse MALDI‐TOF‐MS afin de déterminer la composition des peptides, et dans la mesure du possible, un séquençage de novo a donné des données de séquence des peptides. Une base de données interne des protéines capillaires humaines incorporant 98 séquences de protéines annotées a aidé l'analyse MS. Résultats: les gels 2DE de JRH extraits par le tris (2‐carboxyéthyl) ont amélioré la résolution et le nombre de la kératine et du KAP par rapport à ceux du JRH extrait par le dithiothréitol et des gels bidimensionnels fabriqués commercialement. Les gels 2DE à coloration argentée des ensembles de JHH raides ou bouclés étaient remarquablement similaires. La sur‐coloration pour révéler les protéines de base a provoqué une mauvaise résolution des principales classes de protéines acides. Les comparaisons logicielles des 59 protéines résolues ont révélé que deux présentaient une différence significative d'abondance entre les cheveux bouclés et raides, mais en quantités insuffisantes pour une analyse MS. La MS a identifié douze protéines provenant d'un gel 2DE coloré CBBG JRH : six kératines de type II, trois kératines de type I et trois protéines à forte teneur en soufre. Huit autres étaient des isoformes conformationnels potentiels et des variantes isoélectriques des protéines identifiées, ramenant le total à 20 protéines identifiées ou partiellement identifiées. Conclusion: l'extraction des cheveux humains à la racine avec du tris (2‐carboxyéthyl) phosphine améliore la résolution des protéines et permet de visualiser plus de protéines sur les gels 2DE grand format. Les deux différences de protéines mineures entre les duplicatas des gels 2DE JHH raides ou bouclés étaient peu susceptibles de changer la structure des fibres de cheveux raides à bouclés. Les résultats de la MS ont confirmé qu'il existe plusieurs isoformes de diverses protéines capillaires. Une faible couverture de séquence a empêché la distinction entre les protéines homologues de poids moléculaire similaire.